Parental stress and resilience in CHD: a new frontier for health disparities research - Lisanti, Amy J. (Cardiology in the young, 2018)
Parental stress is a universal experience for parents who have children diagnosed with CHD and has been studied within the context of the child’s illness, but not through a broader health disparity lens. This paper provides a thorough synthesis of the current literature on parental stress addressing disparities in parents of children with CHD. Several theories and models from within this literature are described and a new comprehensive framework, the Parental Stress and Resilience in CHD Model, is presented. Future research and clinical implications are discussed.